Prophylactic endotracheal intubation prior to emergency endoscopy for acute esophagogastric variceal hemorrhage: a retrospective single center study - Yi-Ru Zhao; Ya-Ting Wang; Xue-Qun Zhang (BMC Gastroenterology)
Abstract Background Prophylactic endotracheal intubation (PEI) is widely performed before emergency endoscopy in patients with acute esophagogastric variceal bleeding (AEVB). However, its safety and benefits remain controversial. This study aims to evaluate the efficacy of PEI in patients with AEVB and the appropriate extubation time. Methods Patients with AEVB and underwent emergency endoscopy at The First Affiliated Hospital (04/2011-09/2023) were included and divided into PEI and non-PEI groups. Clinical outcomes included cardiopulmonary complications, incidence of automatic discharge or in-hospital death, hospital and intensive care unit (ICU) length of stay (LOS), and rebleeding rate in one month. Extubation time in patients with PEI was also analyzed. Results Three patients had massive aspiration without PEI. Among 141 patients, 97 (68.8%) received PEI. Pneumonia and pulmonary edema were more frequent in the PEI group (42.3% vs. 25.0%; OR = 2.20, 95% CI: 1.00-4.86; P = 0.049; 26.8% vs. 6.8%; OR = 5.00, 95% CI: 1.42–17.55; P = 0.007), and the ICU LOS was also longer (P<0.001). Among patients with PEI, 29 (29.9%) patients were extubated within 24 h, and had a lower incidence of acute respiratory distress syndrome (ARDS) (4.4% vs. 17.2%, P = 0.049; adjusted P = 0.123), lower automatic discharge or in-hospital death rate (2.9% vs. 20.7%, P = 0.008), shorter ICU and hospital LOS (P<0.001). Conclusion PEI prior to emergency endoscopy may not protect patients with AEVB from cardiopulmonary complications or improve their prognosis, but it may prevent severe fatal aspiration. And early extubation appears to be associated with better clinical outcomes.